“Control Químico De Mosca De La Fruta (Anastrepha Spp.) En El Cultivo De Naranja En La Zona De Montalvo, Provincia De Los Ríos, Utilizando Trampas Mcphail Para Su Captura”. - Sánchez Altamirano, Bryan (2018)
VIII. SUMMARY This investigation was carried out in the La Prosperidad Farm, in the Las Mercedes Precinct of the Montalvo Canton of the province of Los Ríos. The experimental area has a humid tropical climate, according to the Holbridge classification, with an annual average temperature of 24.2ºC, a precipitation of 3369 mm / year, relative humidity of 85%, and 892.7 hours of annual average heliophany. The objective of this work was to establish the effectiveness of the Spinosad insecticide in the McPhail trap on the control of the fruit fly in the orange crop; Identify the correct dose of Spinosad in the McPhail trap for effective control of the fruit fly and determine the most cost-effective treatment. The treatments studied were McPhail + Protein + Insecticide in doses of 1500 + 1500 cc / ha; 1500 + 1600 cc / ha; 1500 + 1700 cc / ha; McPhail + Protein in doses of 1500 cc / ha and McPhail + Insecticide in doses of 1600 cc / ha. The experimental design of random blocks with 5 treatments and 5 repetitions was used. To determine the statistical difference between treatments, the Tukey test was performed at 95% reliability. To determine the effect of the treatments, it was evaluated 20, 40 and 60 days after reserving the McPhail traps, effectiveness of the insecticide, affectation of fruits per tree and per plant, yield and economic analysis. Based on the analysis and interpretation of the results obtained, it was determined that the chemical control of the fruit fly (Anastrepha spp.) In the orange crop, using McPhail traps for its capture, obtained good results in all its treatments; the highest number of adults of fruit fly (Anastrepha spp.) was presented in the evaluation at 40 days, decreasing at 60 days; the use of McPhail + Protein in a dose of 1500 cc / ha registered a greater affectation of fruits per tree; the treatment of McPhail + Protein + Insecticide in doses of 1500 + 1600 cc / ha and McPhail + Protein + Insecticide in doses of 1500 + 1700 cc / ha presented greater affectation of fruits / plant and the highest yield and net benefit was observed in the treatment that was used McPhail + Protein in doses of 1500 cc / ha with 37356,2 kg / ha and net benefit of $ 1895,1.